Pengaruh E-wom, Online Customer Review, E-trust dan Gaya Hidup Terhadap Keputusan Pembelian Pada Keranjang Kuning Tiktok Shop - Widya Septria Marni; Yesi Elsandra (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
The rapid development of digital technology has transformed consumer behavior, including the increasing trend of online shopping through social media platforms such as TikTok Shop. This study aims to analyze the influence of Electronic Word of Mouth (e-WOM), Online Customer Review, e-Trust, and Lifestyle on Purchase Decisions through the Yellow Cart feature on the TikTok Shop application. The research employed a quantitative approach with purposive sampling. The sample consisted of 96 respondents residing in Padang Timur District who had made at least one purchase via TikTok Shop. Data were collected through a questionnaire distributed via Google Forms and analyzed using multiple linear regression. The results show that e-WOM, Online Customer Review, e-Trust, and Lifestyle have a positive and significant effect on purchase decisions, both partially and simultaneously. These findings provide practical implications for TikTok Shop sellers to effectively manage customer reviews, build consumer trust, and align marketing strategies with the lifestyle of their target market.